Toxoplasmosis en el embarazo. Revisión de caso.: Toxoplasmosis during pregnancy. A review of cases (La U Investiga, 2024)
Toxoplasmosis is an infection caused by the protozoan parasite Toxoplasma gondii, known as one of the most widespread zoonoses in the world, during pregnancy it can lead to various complications. This infection can be acquired during childhood or adolescence and remain latent, likewise, during pregnancy this infection in the mother can be reactivated and transmitted to the fetus, thus appearing congenital toxoplasmosis. For the diagnosis of this infection we must be guided by the interrogation, serological tests and even molecular tests. Regarding serological tests, it is considered the gold standard to determine this pathology by identifying IgM and IgG antibodies. IgM antibodies will be detectable from day 5 after infection, with their maximum levels in 1 to 2 months. On the other hand, IgG antibodies will be detectable after 1 to 2 weeks of infection, thus reaching maximum levels between 3 to 6 months. High IgG avidity is a hallmark of chronic infection (>4 months of age) and low avidity in early gestation essentially rules out fetal risk, confirmatory management will be based on DNA molecular testing for Toxoplasma Gondi in amniotic fluid. This case review seeks to demonstrate the existence of toxoplasmosis in pregnant women in our environment, its pathogenesis, evaluation and management, highlighting the role of the health team to reduce the risk of maternal-fetal complications, both prenatally and postnatally.